Production of Knowledge and Geographically Mediated Spillovers from Universities: Spatial Econometric Perspective and Evidence from Austria - Manfred M. Fischer; Attila Varga (European Regional Science Association (ERSA), 2001)
The paper sheds some light on the issue of geographically mediated knowledge spillovers from university research activities to regional knowledge production in the high tech sector in Austria. Knowledge spillovers occur because knowledge created by university is typically not contained within that institution, and thereby creates value for others. The conceptual framework for analysing geographic spillovers of university research on regional knowledge production is derived from Griliches (1979). It is assumed that knowledge production in the high tech sector essentially depends on two major sources of knowledge: the university research that represents the potential pool of knowledge spillovers and R&D performed by the high tech sector itself. Knowledge is measured in terms of patents, university research and R&D in terms of expenditures. We refine the standard %0D knowledge production function by modelling research spillovers as a spatially discounted external stock of knowledge. This enables us to capture local and interlocal spillovers. Using district-level data and employing spatial econometric tools evidence is found of university research spillovers that transcend the geographic scale of the political district in Austria. It is shown that geographic boundedness of the spillovers is linked to a decay effect. Reference Griliches Z. (1979): Issues in Assessing the Contribution of Research and Development to Productivity Growth, Bell Journal of Economics 10, 92-116
Keywords: 330